Menerapkan Pasal 18B Ayat (1) UUD 1945: Diskursus tentang Konstitusionalitas Pemerintahan Daerah Khusus Ibu Kota Nusantara - Sadiawati, Diani; Setiadi, Wicipto; Hanggawan, Miftah Farid (Jurnal Penelitian Hukum De Jure, 2025)
Law No. 3 of 2022 on the National Capital, as amended by Law No. 21 of 2023, has sparked legal and academic debates, particularly regarding its constitutionality. Despite six judicial review petitions in the Constitutional Court, the Special Regional Government of Nusantara Capital (Pemdasus Ibu Kota Nusantara) has not been comprehensively assessed. This study examines its constitutionality based on the 1945 Constitution (UUD 1945), global practices, and Constitutional Court rulings, focusing on three key issues: the nomenclature of Nusantara Capital, the status and leadership appointment of the Nusantara Capital Authority, and the absence of a Regional People's Representative Council (DPRD). Using a juridical-normative approach, this study analyzes UUD 1945, the National Capital Law, Constitutional Court decisions, and academic literature. The findings highlight three main points. First, Nusantara’s nomenclature aligns with Article 18B(1) of UUD 1945, which recognizes special regions. Second, the status and leadership appointment mechanism of the Nusantara Capital Authority do not violate Article 18(4), as confirmed in Constitutional Court Decision No. 11/PUU-IV/2008. Third, the absence of a DPRD is constitutionally valid since special regions allow institutional variations, as affirmed in Constitutional Court Decisions No. 81/PUU-VIII/2010 and No. 11/PUU-IV/2008. In conclusion, Nusantara’s governance is constitutionally grounded in Article 18B(1) of UUD 1945 and relevant Constitutional Court rulings. Its flexible institutional design remains valid as long as it is legally established.